2006
DOI: 10.1016/j.jsbmb.2006.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acetylation, polymerase phosphorylation, and DNA unwinding in glucocorticoid receptor transactivation

Abstract: Varying the concentration of selected factors alters the induction properties of steroid receptors by changing the position of the dose-response curve (or the value for half-maximal induction = EC 50 ) and the amount of partial agonist activity of antisteroids. We now describe a rudimentary mathematical model that predicts a simple Michaelis-Menten curve for the multi-step process of steroid-regulated gene induction. This model suggests that steps far downstream from receptor binding to steroid can influence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 89 publications
(187 reference statements)
5
43
0
Order By: Relevance
“…A recurrent theme with these modulatory proteins is that the V max can be altered independently of EC 50 and partial agonist activity Jr., 1993;Szapary et al, 1996;Szapary et al, 1999;Chen et al, 2000;Zeng et al, 2000;Giannoukos et al, 2001;Song et al, 2001;He et al, 2002;Kaul et al, 2002;Wang et al, 2004a;Wang et al, 2004b;Cho et al, 2005;Kim et al, 2006). This phenomenon is again observed here with GMEB-2 (Table 3A).…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…A recurrent theme with these modulatory proteins is that the V max can be altered independently of EC 50 and partial agonist activity Jr., 1993;Szapary et al, 1996;Szapary et al, 1999;Chen et al, 2000;Zeng et al, 2000;Giannoukos et al, 2001;Song et al, 2001;He et al, 2002;Kaul et al, 2002;Wang et al, 2004a;Wang et al, 2004b;Cho et al, 2005;Kim et al, 2006). This phenomenon is again observed here with GMEB-2 (Table 3A).…”
Section: Discussionsupporting
confidence: 63%
“…In this study, each factor (GME, GMEB-2, Ubc9, and STAMP) that we have previously reported to modulate the EC 50 , partial agonist activity, and V max of GR transactivation Kaul et al, 2000;Zeng et al, 2000;He et al, 2002;Kaul et al, 2002;Cho et al, 2005;Kim et al, 2006;) is found to have some different effect on PRmediate induction or receptor binding under identical transient transfection conditions (Table 3A). Assay conditions under which the GME alters all three properties of GRs have negligible, if any effect, on PRs.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Possible biological mechanisms are that a cofactor could bind transiently to DNA but affect the DNA state (e.g., methylation, ubiquitination, uncoiling, untwisting, etc. ), facilitate the binding of another cofactor, or alter the mRNA state during translation (6,10,11). Considerable experimental evidence has been advanced in support of transient binding (dubbed "hit and run") of GR to endogenous genes (12,13).…”
Section: If [R] + [Rs] + [Rsd] = R T Can Be Replaced By [R] + [Rs] = mentioning
confidence: 99%